Ultrasound-Targeted Microbubble Destruction: Modulation in the Tumor Microenvironment and Application in Tumor Immunotherapy - Han, Ye; Sun, Jiawei; Wei, Hong; Hao, Jiarong; Liu, Weiyao; Wang, Xiaolei (Frontiers in Immunology, 2022)
Tumor immunotherapy has shown strong therapeutic potential for stimulating or reconstructing the immune system to control and kill tumor cells. It is a promising and effective anti-cancer treatment besides surgery, radiotherapy and chemotherapy. Presently, some immunotherapy methods have been approved for clinical application, and numerous others have demonstrated promising in vitro results and have entered clinical trial stages. Although immunotherapy has exhibited encouraging results in various cancer types, however, a large proportion of patients are limited from these benefits due to specific characteristics of the tumor microenvironment such as hypoxia, tumor vascular malformation and immune escape, and current limitations of immunotherapy such as off-target toxicity, insufficient drug penetration and accumulation and immune cell dysfunction. Ultrasound-target microbubble destruction (UTMD) treatment with local ultrasound irradiation can help reduce immunotherapy-related adverse events. Using the ultrasonic cavitation effect of microstreaming, microjets and free radicals, UTMD can cause a series of changes in vascular endothelial cells, such as enhancing endothelial cells' permeability, increasing intracellular calcium levels, regulating gene expression, and stimulating nitric oxide synthase activities. These effects have been shown to promote drug penetration, enhance blood perfusion, increase drug delivery and induce tumor cell death. UTMD, in combination with immunotherapy, has been used to treat melanoma, non-small cell lung cancer, bladder cancer, and ovarian cancer. In this review, we summarized the effects of UTMD on tumor angiogenesis and immune microenvironment, and discussed the application and progress of UTMD in tumor immunotherapy.